Golgi and plasma membrane pools of PI(4)P contribute to plasma membrane PI(4,5)P2 and maintenance of KCNQ2/3 ion channel current - Dickson, Eamonn J; Jensen, Jill B; Hille, Bertil (Proceedings of the National Academy of Sciences - PNAS, 2014)
Plasma membrane (PM) phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2] regulates the activity of many ion channels and other membrane-associated proteins. To determine precursor sources of the PM PI(4,5)P2 pool in tsA-201 cells, we monitored KCNQ2/3 channel currents and translocation of PHPLCδ1 domains as real-time indicators of PM PI(4,5)P2, and translocation of PHOSH2×2, and PHOSH1 domains as indicators of PM and Golgi phosphatidylinositol 4-phosphate [PI(4)P], respectively. We selectively depleted PI(4)P pools at the PM, Golgi, or both using the rapamycin-recruitable lipid 4-phosphatases. Depleting PI(4)P at the PM with a recruitable 4-phosphatase (Sac1) results in a decrease of PI(4,5)P2 measured by electrical or optical indicators. Depleting PI(4)P at the Golgi with the 4-phosphatase or disrupting membrane-transporting motors induces a decline in PM PI(4,5)P2. Depleting PI(4)P simultaneously at both the Golgi and the PM induces a larger decrease of PI(4,5)P2. The decline of PI(4,5)P2 following 4-phosphatase recruitment takes 1-2 min. Recruiting the endoplasmic reticulum (ER) toward the Golgi membranes mimics the effects of depleting PI(4)P at the Golgi, apparently due to the trans actions of endogenous ER Sac1. Thus, maintenance of the PM pool of PI(4,5)P2 appears to depend on precursor pools of PI(4)P both in the PM and in the Golgi. The decrease in PM PI(4,5)P2 when Sac1 is recruited to the Golgi suggests that the Golgi contribution is ongoing and that PI(4,5)P2 production may be coupled to important cell biological processes such as membrane trafficking or lipid transfer activity.